OPTIMASI PEMBANGUNAN DESA: Kajian Kemampuan Manajemen Kepala Desa di Malalanda Buton Utara - Ninik Endang Purwati; La Ode Agus Said; Selmieta (Halu Oleo University, 2023)
The purpose of this research is to evaluate the village chief's managerial skills in carrying out village development (a study in Malalanda village, Kulisusu District, North Buton Regency). A qualitative descriptive research methodology including observation, interview, and documentation was applied in this study. The findings of this research suggest that the Malalanda village head utilizes four (four) management roles to govern village development. Planning is the first. Holding village development meetings (musrembang) with the community is the first step in the development process in Malalanda village. Next, arrange. The village chief put together a special team to rebuild the community's development plans based on the outcomes of the development planning meeting with them. Finally, The Malalanda village chief led the locals or village authorities in putting development initiatives like intercommunal cooperation and community service into action. And finally, oversight. The village chief of Malalanda often makes direct visits to the sites of activities in order to monitor and oversee the performance of local authorities as they execute the development.